FUNCTIONAL ANALYSIS AND TREATMENT OF ELOPEMENT ACROSS TWO SCHOOL SETTINGS - Lang, Russell (The Society for the Experimental Analysis of Behavior, 2010)
The elopement of a child with Asperger syndrome was assessed using functional analyses and was treated in two school settings (classroom and resource room). Functional analyses indicated that elopement was maintained by access to attention in the resource room and obtaining a preferred activity in the classroom. Attention- and tangible-based interventions were compared in an alternating treatments design in both settings. Results validated the findings of the functional analyses. Implications for the assessment and treatment of elopement are discussed.